Predicting material consumption in a Circular Economy oriented design methodology for pedestrian and cycling bridges. Issue 1 (1st September 2022) - Anastasiades, K; Audenaert, A; Blom, J
Abstract: A Circular Economy (CE) oriented design methodology for pedestrian and cycling bridges that takes the 4Rs of the CE -Reduce, Reuse, Recycle, Recover- as basis needs to be developed. The first R, Reduce, is mostly neglected, even though it is the most important R in the CE. Nevertheless, a CE oriented design methodology also needs to consider and formalise Reduce. It is proposed to do this by measuring the material efficiency of a structure. Therefore, a reference volume of material needs to be found. This paper proposes a methodology to predict the necessary amount of material needed for the bridge structure. The methodology takes the theory of the morphological indicators as basis. Morphological indicators are used in the conceptual design phase to find the most efficient structural typology and global dimensions. However, it was found that the volume indication that results from these morphological indicators is not realistic. The main reasons are that they consider a fully stressed state for each component, and they do not consider standard profile sections. Therefore, two correction curves are proposed to correct the volume obtained from the morphological indicators into a realistic one. The limitations of this study are that it only focusses on Warren truss bridges and only considers vertical service loads. Further research will have to focus on incorporating other types of trusses and other structural typologies like arched, suspension and cable-stayed bridges. In addition, more loads like wind and snow that can act on bridges need to be considered.